Metaphors of Economic and Financial Crisis: Identified, Interpreted and Explained - Cibulskienė, Jurga (Respectus Philologicus, 2012)
The aim of this study is to analyze how the economic and financial crisis in Lithuania is metaphorically conceptualized by three sociopolitical groups, i.e., the leading political party (the Conservatives), the Opposition and the media, with a primary focus on the methodological issues of metaphor analysis. The analysis is based on a three-step procedure originally suggested by Charteris-Black: first, linguistic metaphors are identified in the discourse; next, they are interpreted in relation to their underlying conceptual metaphors; and finally, they are explained—or, in other words, they are analysed from a rhetorical perspective (Identified → Interpreted → Explained). This paper focuses mainly on the first stage of analysis and addresses different problems which the researcher faces while undertaking metaphor analysis. The discussion of the procedure of metaphor identification and interpretation is supported with factual data and statistics. Furthermore, the paper outlines directions for future research into crisis metaphors.
Keywords: economic and financial crisis; linguistic and conceptual metaphors; methodology of metaphor analysis